2007
DOI: 10.1016/j.cbpa.2006.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone stimulates hatching of late-term tree lizard embryos

Abstract: The regulation of hatching in oviparous animals is important for successful reproduction and survival, but is poorly understood. We unexpectedly found that RU-486, a progesterone and glucocorticoid antagonist, interferes with hatching of viable tree lizard (Urosaurus ornatus) embryos in a dosedependent manner and hypothesized that embryonic glucocorticoids regulate hatching. To test this hypothesis, we treated eggs with corticosterone (CORT) or vehicle on Day 30 (85%) of incubation, left other eggs untreated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2009
2009
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 42 publications
0
14
1
Order By: Relevance
“…Accordingly, the observed cortisol-induced eVects may represent an adaptive mechanism by which mothers communicate information about the prevailing environment to their oVspring to ensure their immediate survival. Similar hormonally mediated maternal eVects that induce a transition between life stages to avoid deadly conditions or deteriorated environments have been demonstrated in mammals, amphibians and reptiles (Denver 1997;Crespi and Denver 2005;Weiss et al 2007), illustrating the beneWcial eVects of maternal glucocorticoids in shaping the neuroendocrine responses of oVspring, albeit at the potential cost of reduced Wtness later in life.…”
Section: Discussionmentioning
confidence: 58%
“…Accordingly, the observed cortisol-induced eVects may represent an adaptive mechanism by which mothers communicate information about the prevailing environment to their oVspring to ensure their immediate survival. Similar hormonally mediated maternal eVects that induce a transition between life stages to avoid deadly conditions or deteriorated environments have been demonstrated in mammals, amphibians and reptiles (Denver 1997;Crespi and Denver 2005;Weiss et al 2007), illustrating the beneWcial eVects of maternal glucocorticoids in shaping the neuroendocrine responses of oVspring, albeit at the potential cost of reduced Wtness later in life.…”
Section: Discussionmentioning
confidence: 58%
“…Radder et al (2008) posited that the observed premature oviposition by CORT-treated females might be adaptive in terms of protecting the eggs from the possible harmful effects of CORT. The implication of this finding is that tree lizards are unlikely to develop to fullterm in extremely high-CORT environments (Weiss et al, 2007). There is also evidence that super-physiological levels of CORT present in egg yolk at the time of oviposition reduce hatching success in U. stansburiana (Johnston & Moore, unpublished data; Lucas & Weiss, unpublished data; both cited in Weiss et al, 2007), a finding that was attributed to the gross detrimental effects of CORT on the embryo rather than on the hatching event itself (Weiss et al, 2007).…”
Section: Mothers and Offspringmentioning
confidence: 95%
“…At oviposition, CORT-treated females had significantly higher CORT levels (mean ¼ 246.2 ng/ml) than did control females (79.0 ng/ml), although CORT levels in the egg yolk of offspring were unaffected by maternal treatment. There is also evidence that super-physiological levels of CORT present in egg yolk at the time of oviposition reduce hatching success in U. stansburiana (Johnston & Moore, unpublished data; Lucas & Weiss, unpublished data; both cited in Weiss et al, 2007), a finding that was attributed to the gross detrimental effects of CORT on the embryo rather than on the hatching event itself (Weiss et al, 2007). On the other hand, in the side-blotched lizard, U. stansburiana, treatment of gravid females with a low dose (imitated high-end baseline physiological levels) or a high dose (imitated stress-related levels; i.e., equal to or greater than double baseline levels) of CORT delivered from implants did not accelerate or delay the timing of egg laying .…”
Section: Mothers and Offspringmentioning
confidence: 99%
See 2 more Smart Citations